IMPLEMENTATION OF EARLY WARNING SYSTEM IN NURSING WARD: A LITERATURE REVIEW - Meli Diana; Dimas Hadi Prayoga; Dini Prastyo Wijayanti (LPPM Politeknik Kesehatan Kerta Cendekia, 2021)
Hospital service is a process that involves all elements in the hospital including nurses and inpatient rooms or nursing wards. Different inpatient conditions will be treated in separated wards, by the same token patients with unstable conditions are admitted in intensive care units, this procedure aims to reduce the mortality incidence due to sudden cardiac arrest, therefore early detection of patients clinical deterioration using the early warning score system performed by the nurse in the nursing wards is required. This review aims to describe the importance of the early warning system in the nursing wards. The data was obtained from international journal providers s from data base search based on Scopus, Ebscohot: CINHL, Proquest, Springerlink, Google scholar, and Midline. We used the keyword "Early Warning System" or "Early Warning Score" with a search range in 2016-2021. The search results in 127 articles. Language selection was performed as all journals found were in English. Here, we will review 10 articles. Implementation of early warning score in nursing ward is expected to improve the quality of service to patients and reduce the mortality rate. Early detection clinical emergency or known as the Early Warning Score System (EWSS) is the application of a scoring system for early detection of patient's condition before a worsening situation occurs. The implementation of this scoring system is necessary due to the high rate of deterioration of patient conditions that requiring immediate management to prevent profound deterioration and its subsequent adverse effect.